2011
DOI: 10.5415/apallergy.2011.1.3.130
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Aspergillus sinusitis and its association with allergic bronchopulmonary aspergillosis

Abstract: Allergic Aspergillus sinusitis (AAS) is a three decade old clinicopathologic entity in which mucoid impaction akin to that of allergic bronchopulmonary aspergillosis (ABPA) occurs in the paranasal sinuses. Features such as radiographic evidence of pansinusitis, passage of nasal plugs and recurrent nasal polyposis in patients with an atopic background is suggestive of AAS. Histopathlogic confirmation from the inspissated mucus is a sine qua non for the diagnosis. Heterogeneous densities on computed tomography o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…The common presenting symptoms were nasal obstruction (100%), headache (83%), nasal discharge (66%), facial pain (50%), olfactory disturbance (41%), halitosis (33%), epistaxis (25%) and fever (16%) which coincided with the study done by Chakrabartiet al 10 The associated factors were found to be allergy (66%) and asthma (16%) which coincided with the study done by Chandramani Panjabi et al 11 The risk factors associated were found to be diabetes mellitus (33%), usage of immunosuppressive drugs (8%). The prospective study done by Amin et al, 12 found underlying immunocompromised state in the form of haematological malignancy and poorly controlled diabetes mellitus in 22.2% of cases.…”
Section: Discussionsupporting
confidence: 70%
“…The common presenting symptoms were nasal obstruction (100%), headache (83%), nasal discharge (66%), facial pain (50%), olfactory disturbance (41%), halitosis (33%), epistaxis (25%) and fever (16%) which coincided with the study done by Chakrabartiet al 10 The associated factors were found to be allergy (66%) and asthma (16%) which coincided with the study done by Chandramani Panjabi et al 11 The risk factors associated were found to be diabetes mellitus (33%), usage of immunosuppressive drugs (8%). The prospective study done by Amin et al, 12 found underlying immunocompromised state in the form of haematological malignancy and poorly controlled diabetes mellitus in 22.2% of cases.…”
Section: Discussionsupporting
confidence: 70%
“…The radiological finding suggestive of AAS includes hyperdense lesions, ‘star-filled sky’ or ‘ground glass’ pattern. These occur due to the presence of high-density mineral element produced by the fungal elements [ 38 ]. The occurrence of upper airways symptoms and sinusitis has been documented in children with asthma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of appropriate therapy could alter the natural course of the disease and prevent endstage lung fibrosis [61]. Furthermore, the occurrence of AAS in ABPA and ABPA in AAS should always be investigated [186,215].…”
Section: Discussionmentioning
confidence: 99%